Selective Inactivation of Socs3 in SF1 Neurons Improves Glucose Homeostasis without Affecting Body Weight - Zhang, Ren (The Endocrine Society, 2008)
Suppressor of cytokine signaling 3 (Socs3) has been identified as a mediator of central leptin resistance, but the identity of specific neurons in which Socs3 acts to suppress leptin signaling remains elusive. The ventromedial hypothalamus (VMH) was recently shown to be an important site for leptin action because deleting leptin receptor within VMH neurons causes obesity. To examine the role of VMH Socs3 in leptin resistance and energy homeostasis, we generated mice lacking Socs3 specifically in neurons positive for steroidogenic factor 1 (SF1), which is expressed abundantly in the VMH. These mice had increased phosphorylation of signal transducer and activator of transcription-3 in VMH neurons, suggesting improved leptin signaling, and consistently, food intake and weight-reducing effects of exogenous leptin were enhanced. Furthermore, on either chow or high-fat diets, these mice had reduced food intake. Unexpectedly, energy expenditure was reduced as well. Mice lacking Socs3 in SF1 neurons, despite no change in body weight, had improved glucose homeostasis and were partially protected from hyperglycemia and hyperinsulinemia induced by high-fat diets. These results suggest that Socs3 in SF1 neurons negatively regulates leptin signaling and plays important roles in mediating leptin sensitivity, glucose homeostasis, and energy expenditure.